Transformation of random lasing to Fabry-Perot lasing: observation of high temperature lasing from carbon dots - Ni, Yiqun; Li, Xiangyang; Liang, Wenqing; Zhang, Shaofeng; Xu, Xuesong; Li, Zhenyuan; Li, Ling; Shao, Yonghong; Ruan, Shuangchen; Zhang, Wenfei (Nanoscale, 2021)
Carbon dots (CDs), a subject of academic research, have attracted intense attention due to their intrinsic merits of high stability, low cost, and low toxicity. However, the absence of highly efficient red-emitting CDs restricts their application in a variety of areas including lasers. In this work, red emissive CDs (R-CDs) with a quantum yield as high as 66.7% were prepared using 1,3-dihydroxynaphthalene as the initial source. It is found that the superior optical properties of R-CDs are attributed to the high oxidation degree and high ratio of hydroxyl functional groups on the surface of CDs. Red emissive random lasing at 612 nm was realized from a microcavity by using the R-CDs/epoxy composite as the gain medium at room temperature. Simultaneously, the transformation of random lasing to Fabry-Perot lasing in the same laser cavity at 250 °C was observed. This is on account of the declining optical gain which is insufficient to support random lasing in the microcavity at high temperatures. As a result, CD based Fabry-Perot lasing was achieved at a temperature as high as 250 °C for the first time. Red emissive random lasing at 612 nm was realized from a planar microcavity using CDs as the gain medium at room temperature. Simultaneously, the transformation of random lasing to Fabry-Perot lasing in the same laser cavity at 250 °C was observed.